High-strength solidified soil, solidified soil road surface layer and construction process thereof

CN118908690BActive Publication Date: 2026-10-23SHENZHEN JUAN CONSTR TECH CO LTD +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410982178.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2026-10-23
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

[0003]现有的固化土,一般强度较低,抗压强度不足5MPa,在道路建设中,只能作为基层

Benefits of technology

1、由于本申请采用黄泥、豆砾石和细砂等作为原料,并以水泥、硅酸钠和碳酸钙三种原料作为土壤固化剂,由于水泥能产生水化作用,形成氢氧化钙和C-S-H凝胶,并且硅酸钠和碳酸钙能与水泥反生反应,形成硅酸钙凝胶等,粘结固化土,填充到固化体的缝隙中,从而使土壤被固结,且不易产生体积收缩。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004956398050000081
    Figure BDA0004956398050000081
  • Figure BDA0004956398050000091
    Figure BDA0004956398050000091
  • Figure BDA0004956398050000092
    Figure BDA0004956398050000092
Patent Text Reader

Abstract

The application relates to the field of civil engineering materials, and particularly discloses a high-strength solidified soil, a solidified soil road surface layer and a construction process thereof. The high-strength solidified soil comprises the following raw materials in parts by weight: 300-1000 parts of a solidifying agent, 0-600 parts of fine sand, 300-3500 parts of yellow mud, 0-500 parts of bean gravel and 250-500 parts of water; the solidifying agent comprises cement, sodium silicate and calcium carbonate in a mass ratio of 7-8:1-1.5:1-1.5; the solidified soil road surface layer comprises a base layer containing waste brick particles and a high-strength solidified soil layer; and the high-strength solidified soil layer is formed by laying and rolling the high-strength solidified soil on the base layer. The high-strength solidified soil is compact in structure, high in strength and capable of being used as a road surface layer alone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of civil engineering materials technology, and more specifically, it relates to a high-strength solidified soil, a solidified soil road surface layer, and its construction process. Background Technology

[0002] Stabilized soil is a geotechnical engineering material. With the application of soil stabilizers, the physical and mechanical properties of stabilized soil have been improved, making it a new type of geotechnical engineering material with applications in road construction, tidal flat reclamation, river and lake management, water conservancy projects, and farmland construction. For example, in road construction, traditional methods require large amounts of sand and gravel. However, with my country's development and environmental protection requirements, many areas are still quarrying, leading to increasingly prominent conflicts between sand and gravel production and the environment, making sand and gravel supply increasingly difficult, and significantly increasing construction costs. Using stabilized soil technology, with stabilized soil as the road base layer, can fully utilize the original soil, requiring little or no sand and gravel. This not only facilitates construction and improves project quality but also saves resources and reduces project costs.

[0003] Existing solidified soil generally has low strength, with a compressive strength of less than 5 MPa, and can only be used as a base layer in road construction. The surface layer still uses traditional asphalt concrete or cement concrete. However, in the construction of solidified soil roads in some urban roads, scenic areas, modern agriculture and animal husbandry, and ecological construction projects, asphalt concrete and cement concrete surface layers are sometimes difficult to use due to various problems such as pollution during construction, difficulty in material supply, high road construction costs, and cumbersome construction processes. Therefore, it is necessary to find a new lightweight road surface material. However, directly using solidified soil as a road surface has too low strength to be used as a standalone road surface layer.

[0004] In response to the aforementioned technologies, there is an urgent need for a type of solidified soil with high strength that can be used independently as a road surface layer. Summary of the Invention

[0005] To improve the compactness and strength of solidified soil, this application provides a high-strength solidified soil, its preparation method, and a solidified soil road surface layer.

[0006] In the first aspect, this application provides a high-strength solidified soil, which adopts the following technical solution: A high-strength solidified soil comprises the following raw materials in parts by weight: 300-1000 parts of solidifying agent, 0-600 parts of fine sand, 300-3500 parts of yellow mud, 0-500 parts of pea gravel, and 250-500 parts of water. The solidifying agent comprises cement, sodium silicate, and calcium carbonate in a mass ratio of 7-8:1-1.5:1-1.5.

[0007] By adopting the above technical solution, using cement, sodium silicate, and calcium carbonate as solidifying agents, sodium silicate, with its good permeability, can quickly penetrate into the solidified soil and react chemically with free calcium and magnesium ions in the soil. Furthermore, the sodium ions in sodium silicate can undergo ion exchange reactions with free calcium and magnesium ions in the soil to form a stable calcium silicate gel, fixing soil particles in place and improving the soil's impermeability and durability. Calcium carbonate mainly works by combining calcium carbonate ions with heavy metal ions in the soil to form insoluble carbonates, thereby reducing the flow of heavy metals in the soil. Cement solidifies the soil and improves its pH and structure. Through hydration, cement reacts with water in the slurry to form various hydrates, which then undergo a series of physicochemical reactions with soil particles, improving the soil's engineering properties. Specifically, minerals such as tricalcium silicate and dicalcium silicate in cement react with water to form hydrates such as calcium hydroxide and hydrated calcium silicate. These hydrates form fine crystals in the soil, filling the pores between soil particles, enhancing the bonding force between particles, and making the soil denser. This, in turn, improves the soil's overall strength, impermeability, bearing capacity, and stability.

[0008] Optionally, the high-strength solidified soil comprises the following raw materials in parts by weight: 950-1000 parts of curing agent, 3450-3500 parts of... Yellow clay, 450-500 parts water, and the curing agent comprising cement, sodium silicate and calcium carbonate in a mass ratio of 8:1:1.

[0009] By adopting the above technical solution, dry-mixed solidified soil is prepared by mixing yellow mud, water and solidifying agent. The resulting solidified soil has high compressive strength and high compactness.

[0010] Optionally, the high-strength solidified soil comprises the following raw materials in parts by weight: 300-400 parts of curing agent, 550-600 parts of fine sand, 300-350 parts of yellow mud, 350-500 parts of pea gravel, and 250-300 parts of water. The curing agent comprises cement, sodium silicate, and calcium carbonate in a mass ratio of 8:1:1.

[0011] By adopting the above technical solution, fine sand, pea gravel, solidifying agent and yellow mud are mixed to make fluid solidified soil. After solidification, it has high strength and good impermeability.

[0012] Optionally, the particle size of the pea gravel is 1-2 cm.

[0013] By adopting the above technical solution, pea gravel, as coarse aggregate, serves as a supporting structure in the solidified soil and, together with fine sand, improves the strength of the solidified soil. If the pea gravel particle size is small and the gradation is poor, more fine sand and yellow clay are needed to fill the voids, resulting in lower flexural strength. As the particle size increases, the gradation becomes more reasonable, resulting in fewer weak points at the interface and improving the flexural strength of the solidified soil. If the particle size increases further, there are even fewer bonding interfaces, and the bonding interface between pea gravel and yellow clay, cement, etc., is a weak point in strength development. The concrete is prone to stress concentration failure, causing the flexural strength to decrease again.

[0014] Optionally, the pea gravel undergoes the following pretreatment: carbide slag, rice husk ash, and water are mixed evenly in a ratio of 1.8-2:1:1.4-1.5 to obtain a slurry; Add the pea gravel to the slurry and stir thoroughly. Then place the slurry-coated pea gravel on a wire mesh and let it stand for 2-3 hours. Then cure it under constant temperature and humidity for 28 days to obtain aggregate. Mix epoxy resin and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane at a mass ratio of 10:0.8-1, add aggregate, stir thoroughly, and let stand for 20-24 hours.

[0015] By adopting the above technical solution, both carbide slag and rice husk ash are solid waste materials. Using both to improve the strength of pea gravel has significant economic benefits. The chemical composition of carbide slag is mainly calcium oxide, with calcium hydroxide and calcite as the main minerals. Rice husk ash is produced by burning rice husks at 500-800℃ in a dilute oxygen environment. It contains a large amount of free silica and has high pozzolanic activity, making it a suitable component of cementitious materials. After mixing, the calcium hydroxide in the carbide slag and the silica in the rice husk ash react in an aquatic environment... The reaction forms CSH gel, so after the pea gravel is fully stirred in the slurry, the slurry coats the pea gravel, reducing its porosity and increasing its density. After hydration and hardening, a coating layer with high bonding strength and good mechanical properties is formed on the surface of the pea gravel, thereby improving its load-bearing capacity and making it less prone to wear and breakage. Then, epoxy resin and curing agent are mixed and coated on the aggregate. The epoxy resin has good hydrophobicity, which can reduce the water absorption and hygroscopicity of the pea gravel, thereby improving the permeability of the solidified soil and enhancing its impermeability.

[0016] Secondly, this application provides a method for preparing a solidified soil road surface layer, which adopts the following technical solution: a solidified soil road surface layer includes a base layer containing waste brick particles and a high-strength solidified soil layer located above the base layer, wherein the high-strength solidified soil layer is formed by laying and compacting high-strength solidified soil on the base layer.

[0017] By adopting the above technical solution, a base layer containing waste brick particles is laid, and high-strength solidified soil is laid on the base layer. After compaction, high-strength solidified soil is formed, which has high strength, simple construction method and low cost.

[0018] Optionally, the solidified soil road surface layer further includes a protective layer located above the high-strength solidified soil layer. The protective layer includes 4-8 parts by weight of silicone emulsion, 0.3-0.5 parts by weight of wear-resistant agent, 0.01-0.02 parts by weight of defoamer, 0.02-0.04 parts by weight of hydrogen-containing silicone oil, 0.1-0.5 parts by weight of silica, and 1-2 parts by weight of water.

[0019] By adopting the above technical solution, it is found that high-strength solidified soil is prone to dusting in sunny weather and slippery in rainy weather, and has insufficient wear resistance. By setting a protective layer on the high-strength solidified soil layer, the organosilicon emulsion interacts with the soil particles in the high-strength solidified soil at a certain thickness, causing the soil particles to adsorb and overlap, forming a dense and impermeable film. This reduces the infiltration capacity of water in the soil, enhances the waterproof and seepage-resistant ability of the road surface layer, and at the same time reduces the dusting phenomenon of the high-strength solidified soil layer. The wear-resistant agent and silica can increase the wet friction of the road surface layer and increase its wear resistance.

[0020] Optionally, the method for preparing the wear-resistant agent includes the following steps: By weight, 2-5 parts clay, 0.5-1.5 parts fly ash and 1.5-3 parts water are mixed, and then 0.04-0.1 parts calcium lignosulfonate are added. After mixing, the mixture is granulated, dried, and ball-milled to obtain spherical particles with a particle size of 100-150 μm. The spherical body is mixed with 0.09-0.1 parts of polyvinyl alcohol, 2.5-6.5 parts of polyimide and 30-40 parts of water to form a mixed slurry; the mixed slurry is spray-granulated, dried and sintered to obtain a wear-resistant agent. The spray drying inlet temperature is 110-115℃, the outlet temperature is 130-135℃ and the flow rate is 60-65ml / min.

[0021] By adopting the above technical solution, fly ash, as an industrial waste, is emitted in huge quantities every year, putting enormous pressure on the ecological environment. Fly ash, mainly composed of silicon, aluminum, and calcium oxides, has a large specific surface area and stable composition, possessing certain properties. Therefore, when mixed with clay and water, it can increase the gelling properties of the clay, forming hard spherical bodies. Moreover, the incorporation of calcium lignin sulfonate improves the strength and impermeability of the spherical bodies. Calcium lignin sulfonate can rearrange clay and fly ash particles through dispersion and bridging, and also fills pores. In addition, through the chemical chain interaction between its hydrophilic groups and the metal cations on the surface of clay particles, lignin is adsorbed onto the surface of clay particles, while the hydrophobic groups form an oily layer around the surface of the clay particles. It has a certain dissipation effect on the surface of clay particles and prevents water from entering. The addition of calcium lignosulfonate can also improve the dispersion uniformity of spherical particles with polyimide and polyvinyl alcohol. When spray granulation is carried out, polyvinyl alcohol acts as a binder. During the atomization process, the mixed slurry forms a high-speed liquid film and breaks into droplets. Due to surface tension, the droplets gradually form spheres and evaporate and dry rapidly, eventually coating the surface of the spheres to obtain granular wear-resistant agent. The coating of polyimide can improve the dispersion of spheres in organosilicon emulsion, so that the wear-resistant agent is evenly distributed in the protective layer. Moreover, polyimide has high mechanical strength, high temperature resistance and chemical stability, and has good wear resistance. Therefore, the wear-resistant agent can effectively improve the wear resistance of road surface layer.

[0022] Optionally, the thickness of the high-strength solidified soil layer is 10-15cm, and the thickness of the protective layer is 10-15mm.

[0023] By adopting the above technical solution, the protective layer is placed on the high-strength solidified soil layer, which can prevent dusting and increase the wear resistance of the high-strength solidified soil layer.

[0024] Thirdly, this application provides a construction process for a solidified soil road surface layer, employing the following technical solution: A construction process for a solidified soil road surface layer includes the following steps: Preparation of the base course: The roadbed is leveled, waste brick particles are laid, and then rolled and compacted to obtain the base course; Preparation of high-strength solidified layer: Lay high-strength solidified soil on the base layer and compact it to obtain a high-strength solidified soil layer with a thickness of 10-15cm; Preparation of protective layer: Mix organosilicon emulsion, defoamer, hydrogen-containing silicone oil, silica and water evenly to prepare a protective liquid. Spray the protective liquid onto the surface of the high-strength solidified soil layer, and then evenly sprinkle the wear-resistant agent on the protective liquid in 2-3 applications. After natural drying, polish to form a protective layer with a thickness of 10-15mm.

[0025] By adopting the above technical solution, after compacting the base layer containing waste brick particles, laying high-strength solidified soil, finally spraying protective liquid, sprinkling wear-resistant agent, drying and grinding, a road surface layer with high strength, good impermeability and wear resistance is obtained. The construction method is simple.

[0026] In summary, this application has the following beneficial effects: 1. Since this application uses yellow mud, pea gravel and fine sand as raw materials, and cement, sodium silicate and calcium carbonate as soil stabilizers, cement can produce hydration to form calcium hydroxide and CSH gel, and sodium silicate and calcium carbonate can react with cement to form calcium silicate gel, etc., which bind and stabilize the soil and fill the gaps in the stabilized body, thereby consolidating the soil and making it less prone to volume shrinkage.

[0027] 2. In this application, carbide slag, rice husk ash and epoxy resin are preferably used to pretreat pea gravel, which reduces the porosity of pea gravel, increases its density, improves its strength, and enhances its surface hydrophobicity, thereby enhancing the impermeability of high-strength solidified soil.

[0028] 3. In this application, a base layer containing waste brick particles is used as the bottom, and high-strength solidified soil is laid and compacted to form a high-strength solidified soil layer. Then, a protective liquid is sprayed and a wear-resistant agent is applied to make a road surface layer with strong crack resistance, high compressive strength, impermeability, and strong wear resistance. It is not easy to produce dust in sunny weather and is not easy to become slippery in rainy weather. Detailed Implementation

[0029] The following embodiments provide a further detailed description of this application.

[0030] Examples of abrasion-resistant agent preparation 1-4 Preparation Example 1: (1) Mix 50g clay, 15g fly ash and 30g water evenly, add 1g calcium lignosulfonate, mix evenly, add to a granulator, granulate, dry, ball mill, and obtain spherical particles with a particle size of 100μm. The clay is bentonite, the fly ash is Grade II fly ash, the fineness is 11.2%, the loss on ignition is 1.2%, the activity index is 76%, and the water requirement ratio is 100%. (2) Mix the spherical body with 1g of polyvinyl alcohol, 65g of polyimide and 400g of water to form a mixed slurry. The polyvinyl alcohol is PVA1788 and the polyimide is selected from Mitsui Chemicals of Japan, model PL450C. (3) Spray granulation of the mixed slurry to obtain wear-resistant agent. The spray drying inlet temperature is 110℃, the outlet temperature is 130℃, the flow rate is 65ml / min, and the atomization speed is 15000rpm.

[0031] Preparation Example 2: (1) After mixing 20g clay, 5g fly ash and 15g water evenly, add 0.4g calcium lignosulfonate, mix evenly, add to a granulator, granulate, dry, ball mill, and obtain spherical particles with a particle size of 150μm. The clay is bentonite, the fly ash is Grade II fly ash, the fineness is 11.2%, the loss on ignition is 1.2%, the activity index is 76%, and the water requirement ratio is 100%. (2) Mix the spherical body with 0.9g of polyvinyl alcohol, 25g of polyimide and 300g of water evenly to form a mixed slurry. The polyvinyl alcohol is PVA1788 and the polyimide is selected from Mitsui Chemicals of Japan, model PL450C. (3) Spray granulation of the mixed slurry to obtain wear-resistant agent. The spray drying inlet temperature is 115℃, the outlet temperature is 135℃, the flow rate is 60ml / min, and the atomization speed is 15000rpm.

[0032] Preparation Example 3: 50g of clay, 15g of fly ash, and 30g of water were mixed evenly, and then 1g of calcium lignosulfonate was added. After mixing evenly, the mixture was added to a granulator, granulated, dried, and ball-milled to obtain a wear-resistant agent with a particle size of 100μm. The clay was bentonite, the fly ash was Grade II fly ash, the fineness was 11.2%, the loss on ignition was 1.2%, the activity index was 76%, and the water requirement ratio was 100%.

[0033] Preparation Example 4: The difference from Preparation Example 1 is that calcium lignosulfonate was not added. Example

[0034] Example 1: A high-strength solidified soil, comprising the following raw materials by weight: 300g solidifying agent, 600g fine sand, 300g yellow mud, 500g pea gravel and 250g water. The solidifying agent comprises 240g Conch brand P.O42.5 silicate cement, 30g anhydrous sodium sulfate and 30g calcium carbonate with a particle size of 400 mesh. The fineness modulus of the fine sand is 2.3 and the particle size of the pea gravel is 2cm.

[0035] Example 2: A high-strength solidified soil, comprising the following raw materials by weight: 400g solidifying agent, 550g fine sand, 350g yellow mud, 350g pea gravel and 30g water. The solidifying agent comprises 320g Conch brand P.O42.5 silicate cement, 40g anhydrous sodium sulfate and 40g calcium carbonate with a particle size of 400 mesh. The fineness modulus of the fine sand is 2.3 and the particle size of the pea gravel is 1cm.

[0036] Example 3: A high-strength solidified soil, comprising the following raw materials by weight: 300g solidifying agent, 600g fine sand, 300g yellow mud, 500g pea gravel and 250g water. The solidifying agent comprises 210g Conch brand P.O42.5 silicate cement, 45g anhydrous sodium sulfate and 45g calcium carbonate with a particle size of 400 mesh. The fineness modulus of the fine sand is 2.3 and the particle size of the pea gravel is 2cm.

[0037] Example 4: A high-strength solidified soil, differing from Example 1 in that the pea gravel undergoes the following pretreatment: Mix 200g of carbide slag, 100g of rice husk ash, and water in a ratio of 2:1:1.5 to obtain a slurry. The average particle size of the carbide slag is 5μm, and the average particle size of the rice husk ash is 8μm. Add 500g of pea gravel to the slurry and stir thoroughly. Then place the slurry-coated pea gravel on a wire mesh and let it stand for 3 hours. Then cure it in a constant temperature and humidity chamber at 20℃ and 95% for 28 days to obtain aggregate. Mix 800g of epoxy resin and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane at a mass ratio of 10:1, add aggregate, stir thoroughly, spread evenly and let stand for 24 hours. The epoxy resin emulsion is selected from Guangzhou Shanghe New Material Technology Co., Ltd., model WEP-6858.

[0038] Example 5: A high-strength solidified soil, differing from Example 1 in that the pea gravel undergoes the following pretreatment: Mix 180g of carbide slag, 100g of rice husk ash, and water in a ratio of 1.8:1:1.4 to obtain a slurry. The average particle size of the carbide slag is 5μm and the average particle size of the rice husk ash is 8μm. Add 500g of pea gravel to the slurry and stir thoroughly. Then place the slurry-coated pea gravel on a wire mesh and let it stand for 2 hours. Then cure it in a constant temperature and humidity chamber at 20℃ and 95% for 28 days to obtain aggregate. Mix 800g of epoxy resin and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane at a mass ratio of 10:0.8, add aggregate, stir thoroughly, spread evenly and let stand for 20 hours. The epoxy resin emulsion is selected from Guangzhou Shanghe New Material Technology Co., Ltd., model WEP-6858.

[0039] Example 6: A high-strength solidified soil, differing from Example 1 in that the pea gravel undergoes the following pretreatment: Mix 200g of carbide slag, 100g of rice husk ash, and water in a ratio of 2:1:1.5 to obtain a slurry. The average particle size of the carbide slag is 5μm, and the average particle size of the rice husk ash is 8μm. Add 500g of pea gravel to the slurry and stir thoroughly. Then place the slurry-coated pea gravel on a wire mesh and let it stand for 3 hours. Finally, cure it in a constant temperature and humidity chamber at 20℃ and 95% for 28 days.

[0040] Example 7: A high-strength solidified soil, differing from Example 1 in that the pea gravel undergoes the following pretreatment: Mix 800g of epoxy resin and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane at a mass ratio of 10:1, add 500g of pea gravel, stir thoroughly, spread evenly and let stand for 24 hours. The epoxy resin emulsion is selected from Guangzhou Shanghe New Material Technology Co., Ltd., model WEP-6858.

[0041] Example 8: A high-strength solidified soil, comprising the following raw materials by weight: 1000g solidifying agent, 3500g yellow mud, 500g water. The solidifying agent comprises 800g cement, 100g sodium silicate and 100g calcium carbonate. The calcium carbonate has a particle size of 400 mesh. The cement is Conch brand PO 42.5 silicate cement.

[0042] Example 9: A high-strength solidified soil, comprising the following raw materials by weight: 950g solidifying agent, 3450g yellow mud, 450g water. The solidifying agent includes 760g cement, 95g sodium silicate and 95g calcium carbonate. The calcium carbonate has a particle size of 400 mesh. The cement is Conch brand P.O42.5 silicate cement.

[0043] Example 10: A high-strength solidified soil, comprising the following raw materials in parts by weight: 1000g solidifying agent, 3500g yellow mud, 500g water, the solidifying agent comprising 700g cement, 150g sodium silicate and 150g calcium carbonate, the calcium carbonate having a particle size of 400 mesh, and the cement being Conch brand P.O42.5 silicate cement.

[0044] Comparative Example Comparative Example 1: A high-strength solidified soil, which differs from Example 1 in that an equal amount of slaked lime is used instead of the solidifying agent.

[0045] Comparative Example 2: A high-strength solidified soil, which differs from Example 1 in that an equal amount of cement is used instead of the curing agent.

[0046] Comparative Example 3: A high-strength solidified soil, which differs from Example 8 in that an equal amount of slaked lime is used instead of the solidifying agent.

[0047] Comparative Example 4: A high-strength solidified soil, which differs from Example 8 in that an equal amount of cement is used instead of the curing agent.

[0048] Application Example I Application Example I-1: A solidified soil road surface layer, comprising a base layer, a high-strength solidified soil layer, and a protective layer in sequential contact, wherein the construction process of the solidified soil road surface layer includes the following steps: S1. Preparation of base course: The roadbed is leveled, waste brick particles are laid, rolled and compacted to obtain the base course. The waste brick particles include two types, 5mm and 15mm, with a mass ratio of 1:2. The thickness of the base course is 25cm. S2. Preparation of high-strength solidified soil layer: According to the raw material dosage in Example 1, mix the raw materials to prepare high-strength solidified soil, lay it on the base layer, and compact it to obtain a high-strength solidified layer with a thickness of 15cm. S3. Preparation of protective layer: Mix 8 kg of silicone emulsion, 0.02 kg of defoamer, 0.04 kg of hydrogen-containing silicone oil, 0.5 kg of silica and 2 kg of water evenly to prepare a protective liquid. Spray the protective liquid onto the surface of the high-strength curing layer. Then, evenly sprinkle 0.5 kg of the wear-resistant agent prepared in Example 1 onto the protective liquid in two applications. After natural drying, polish to form a protective layer with a thickness of 15 mm.

[0049] Application Example I-2: A solidified soil road surface layer, comprising a base layer, a high-strength solidified soil layer, and a protective layer in sequential contact, wherein the construction process of the solidified soil road surface layer includes the following steps: S1. Preparation of base course: The roadbed is leveled, waste brick particles are laid, rolled and compacted to obtain the base course. The waste brick particles include two types, 5mm and 15mm, with a mass ratio of 1:2. The thickness of the base course is 20cm. S2. Preparation of high-strength solidified soil layer: According to the raw material dosage in Example 2, mix the raw materials to prepare high-strength solidified soil, lay it on the base layer, and compact it to obtain a high-strength solidified layer with a thickness of 10cm. S3. Preparation of protective layer: Mix 4 kg of silicone emulsion, 0.01 kg of defoamer, 0.02 kg of hydrogen-containing silicone oil, 0.1 kg of silica and 1 kg of water evenly to prepare a protective liquid. Spray the protective liquid onto the surface of the high-strength curing layer. Then, evenly sprinkle 0.3 kg of the wear-resistant agent prepared in Example 2 onto the protective liquid in 3 applications. After natural drying, polish to form a protective layer with a thickness of 10 mm.

[0050] Application Example I-3: A solidified soil road surface layer, which differs from Application Example I-1 in that, in step S3, the abrasion-resistant agent is prepared by Preparation Example 3.

[0051] Application Example I-4: A solidified soil road surface layer, which differs from Application Example I-1 in that, in step S3, the abrasion-resistant agent is prepared by Preparation Example 4.

[0052] Application Example I-5: A solidified soil road surface layer, which differs from Application Example I-1 in that no wear-resistant agent is added to the protective layer.

[0053] Application Example I-6: A solidified soil road surface layer, which differs from Application Example I-1 in that it does not have a protective layer.

[0054] Application Example I-7: A solidified soil road surface layer, which differs from Application Example I-1 in that the amount of high-strength solidified soil used in Example 8 is adopted in step S2.

[0055] Performance testing I. Performance testing of high-strength curing agent: High-strength cured soil was prepared according to the methods in Examples 1-10 and Comparative Examples 1-4. The compressive strength was tested according to the method in GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" and the permeability coefficient was tested according to GB / T50123-2019 "Standard for Geotechnical Test Methods". The test results are recorded in Table 1.

[0056] Table 1 Performance Tests of High-Strength Solidified Soil The high-strength solidified soil prepared in Examples 1-3 has high compressive strength, which is higher than that when quicklime and cement are used as solidifying agents. It also has a denser structure and better impermeability.

[0057] In Examples 4 and 5, rice husk ash and carbide slag were used to pretreat the pea gravel, which shows that the high-strength solidified soil prepared in Examples 4 and 5 has better performance.

[0058] In Example 6, a slurry made from carbide slag and rice husk ash was used to coat the pea gravel. In Example 7, an epoxy resin emulsion was used to coat the pea gravel. Compared with Example 4, the impermeability of the solidified soil in Example 6 decreased, and the strength of the solidified soil in Example 7 decreased.

[0059] In Examples 8-10, solidified soil was prepared using a curing agent, yellow mud, and water. It can be seen that the solidified soil also has strong compressive strength.

[0060] II. Performance testing of solidified soil road surface layer: Prepare solidified soil road surface layer according to the method in Application Example I1-7, and test it according to the following method. Record the test results in Table 2.

[0061] 1. Wear Amount: A cubic specimen with dimensions of 150mm × 150mm was prepared. During the test, the initial mass m1 of the specimen was the mass of the specimen after 30 revolutions of wear, and the mass m2 of the specimen after wear was the remaining mass of the specimen after 60 revolutions of wear. The wear amount per unit area of ​​the specimen was calculated according to the following formula: G = (m1 - m2) / V, where G is the wear amount per unit area (kg / m²). 2 V is the area of ​​the worn surface (m²). 2 ).

[0062] 2. Seepage height: Tested in accordance with GB / T50082-2009 "Test Methods for Long-Term Performance and Durability of Ordinary Concrete".

[0063] 3. Flexural strength: The compressive strength shall be tested in accordance with the methods in GB / T17671-2021 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".

[0064] Table 2 Performance Tests of Solidified Soil Road Surface Layers Table 2 shows that Application Example I1 and Application Example I-2 use the high-strength solidified soil prepared by the formulations in Example 1 and Example 2 to make high-strength solidified soil layers, and set a protective layer containing wear-resistant agents prepared by Preparation Example 1 and Preparation Example 2 respectively, which can effectively improve the wear resistance, crack resistance and impermeability of the solidified soil road surface layer.

[0065] In Application Example I-3, the wear-resistant agent in the protective layer was prepared in Preparation Example 3, in which polyimide or the like was not used for spray drying. Compared with Application Example I-1, the wear resistance of the solidified soil road surface layer prepared by it decreased, the impermeability was weakened, and the flexural strength was worse.

[0066] In Application Example I-4, the wear-resistant agent prepared in Preparation Example 4 was used. Compared with Preparation Example 1, calcium lignosulfonate was not added. As can be seen from the data comparison in Table 2, the wear resistance of the road surface layer prepared in Application Example I-4 was weakened.

[0067] No wear-resistant agent was added in Application Example I-5, and no protective layer was set in Application Example I-6. The data in Table 2 show that, compared with Application Example I-1, the road surface layers made by Application Example I-5 and Application Example I-6 have increased wear, and weakened impermeability and crack resistance.

[0068] In Application Example I-7, the amount of solidified soil used in Example 8 was adopted. It can be seen that the impermeability and abrasion resistance did not deteriorate significantly, while the flexural strength decreased slightly.

[0069] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-strength solidified soil, characterized in that, The raw materials include the following parts by weight: 300-400 parts curing agent, 550-600 parts fine sand, 300-350 parts yellow mud, 350-500 parts pea gravel, and 250-300 parts water. The curing agent includes cement, sodium silicate, and calcium carbonate in a mass ratio of 8:1:

1. The pea gravel undergoes the following pretreatment: calcium carbide slag, rice husk ash, and water are mixed evenly at a ratio of 1.8-2:1:1.4-1.5 to obtain a slurry; Add pea gravel to the slurry and stir thoroughly. Then place the slurry-coated pea gravel on a wire mesh and let it stand for 2-3 hours. Then cure it under constant temperature and humidity for 28 days to obtain aggregate. Mix epoxy resin and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane at a mass ratio of 10:0.8-1, add aggregate, stir thoroughly, and let stand for 20-24 hours.

2. The high-strength solidified soil according to claim 1, characterized in that: The particle size of the pea gravel is 1-2 cm.

3. A solidified soil road surface layer, characterized in that, It includes a base layer containing waste brick particles and a high-strength solidified soil layer located above the base layer, wherein the high-strength solidified soil layer is formed by laying and compacting the high-strength solidified soil as described in any one of claims 1-2 on the base layer.

4. The solidified soil road surface layer according to claim 3, characterized in that, The solidified soil road surface layer also includes a protective layer located above the high-strength solidified soil layer. The protective layer includes 4-8 parts by weight of organosilicon emulsion, 0.3-0.5 parts by weight of wear-resistant agent, 0.01-0.02 parts by weight of defoamer, 0.02-0.04 parts by weight of hydrogen-containing silicone oil, 0.1-0.5 parts by weight of silica, and 1-2 parts by weight of water.

5. The solidified soil road surface layer according to claim 4, characterized in that, The method for preparing the wear-resistant agent includes the following steps: By weight, 2-5 parts clay, 0.5-1.5 parts fly ash and 1.5-3 parts water are mixed, and then 0.04-0.1 parts calcium lignosulfonate are added. After mixing, the mixture is granulated, dried, and ball-milled to obtain spherical particles with a particle size of 100-150 μm. The spherical object is mixed with 0.09-0.1 parts of polyvinyl alcohol, 2.5-6.5 parts of polyimide and 30-40 parts of water to form a mixed slurry; The mixed slurry is spray-granulated, dried and sintered to obtain a wear-resistant agent. The spray drying inlet temperature is 110-115℃, the outlet temperature is 130-135℃, and the flow rate is 60-65ml / min.

6. The solidified soil road surface layer according to claim 4, characterized in that, The thickness of the high-strength solidified soil layer is 10-15cm, and the thickness of the protective layer is 10-15mm.

7. The construction process of the solidified soil road surface layer according to any one of claims 3-6, characterized in that, Includes the following steps: Preparation of base course: The roadbed is leveled, waste brick particles are laid, and then rolled and compacted to obtain the base course; Preparation of high-strength solidified layer: lay high-strength solidified soil on the base layer and compact it to obtain high-strength solidified soil layer; Preparation of protective layer: Mix organosilicon emulsion, defoamer, hydrogen-containing silicone oil, silica and water evenly to prepare protective liquid. Spray the protective liquid onto the surface of high-strength solidified soil layer. Sprinkle wear-resistant agent evenly on the protective liquid in 2-3 times. After natural drying, polish to form protective layer.

Citation Information

Patent Citations

  • Solidified soil and anti-fouling and anti-seepage treatment method for large coal yards

    CN108191310A